HUBUNGAN ANTARA INDEKS MASSA TUBUH (IMT) DAN OSTEOPOROSIS PADA WANITA PASCAMENOPAUSE - N, Legiran; Tanelvi, Gita (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2015)
Has conducted research relationship of body mass index (BMI) and postmenopausal women with osteoporosis in South Sumatra. Method research with a case control study with cae group was post menopausal women with osteoporosis and control group was similar subjects with in normal bone mineral density (BMD). BMD was resulted by dual-energy x-ray absorptiometry and BMI was defined by Asian population category from World Health Organization (WHO). There were 38 postmenopausal women 52 to 70 years old in each group study. Age matching was performed between groups and data was obtained by chi-square and odds ratio. Result statistical analysis has showed a significant correlation between BMI and osteoporosis (p = 0.004). Based on odds ratio could be concluded that postmenopausal women with low IMT has 4.25 times to suffer osteoporosis. Postmenopausal women with low IMT has risk suffering osteoporosis therefore they should be informed to prevent they self by healthy life style.